Effect of ozonation on simulated freshwater containing Microcystis aeruginosa - Persincula, Mary Rose B. Flores (2009)
Microcystis aeriginosa is one of the most abundant cyanobacteria present worldwide. Water sampling at Laguna de Bay in this study and that of both Laguna Lake Development Authority (LLDA) and Southeast Asian Fisheries Development Cooperation (SEAFDEC), affirm the presence in the lake. Preventing the hazard this may pose to humans who uses water for recreation, aquaculture and drinking, was the motivation for this study. The study determined the effect of ozonation on simulated freshwater containing Microcystis aeuginosa based on its cell count and the chemical oxygen demand (COD). A decline in the cell count was manifested as the ozonation treatment time increases. Ozone attacks both the cells and the organic constituents present in the simulated freshwater. The organic matter was oxidized to form smaller molecular weight compounds. A decline in both dissolved and particulate COD was manifested. The organism also consumes oxygen upon ozonation, manifested greater particulate COD values compared to that of the dissolved COD.
"June 2009."
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Microcystis aeruginosa -- Philippines -- Laguna de Bay; Water -- Purification -- Ozonation -- Philippines; Ozonolysis